Implementasi Evaluasi Hasil Belajar Kognitif Mata Pelajaran Akidah Akhlak MAN 1 Karanganyar - Fatkur Rachmawati; Faisya Abrari Lutrinda; Ilham Nur Safitri; Nurul Latifatul Inayati (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2024)
This study aims to identify the evaluation of cognitive learning outcomes in the subject of akidah akhlak at MAN 1 Karanganyar. The cognitive domain is a learning activity to develop students’ mindset. Likewise, cognitive learning in the subject of moral creed. This research uses a qualitative method with a phenomenological approach through interviews, observation, and documentation as data collection techniques. The data that has been obtained, then analyzed through interactive analysis. Thd results showed that implementation of cognitive learning outcomes for moral creed subjects, teachers not only use written tests to increase students’ knowledge, but also use practical tests. The usual written test is to do the exercise questions. While the practical test, the teacher asks students to memorize selected arguments from each material or chapter. Assessment of the evaluation of student learning outcomes at each grade level results in a comparison of different values. There are still many values found in students who do not have an increase. Keywords: Evaluation, Cognitive, Akidah Akhlak